El método experimental en la enseñanza de las Ciencias Naturales: una forma de llevar la teoría a la práctica - Calva Santin, Lisseth Selena (2024)
The present research deals with The experimental method in the teaching of Natural Sciences: a way of putting theory into practice. The general objective was: To analyze the application of the experimental method in the teaching of Natural Sciences in the fourth grade of basic education at the Dr. Manuel Agustín Cabrera Lozano Educational Unit, in order to fulfill this objective, three specific objectives were carried out, the first one was: To identify the level knowledge presented by the students in the subject of Natural Sciences; the second one considered of: To propose a didactic guide using the experimental method as a means in the acquisition of significant learning in the teaching of Natural Sciences and the third objective: To evaluate the academic performance of students in the subject of Natural after implementing the experimental method as a form of teaching. For the development of the study a descriptive type of research with a mixed approach was used, its design was quasi-experimental, the methods that allowed the collection of information were: deductive, inductive, analytical- synthetic and hermeneutic method; the techniques used were interview and pre and post evaluation, for which the instruments of questions guide and questionnaire were used, in the same way the population was considered to be the fourth grades of basic education of the Educational Unit “Dr. Manuel Agustín Cabrera Lozano”, by means of a probabilistic sampling it was taken into account a parallel conformed by twenty students and a teacher. Manuel Agustin Cabrera Lozano” Educational Unit, by means of a probabilistic sampling, a parallel was taken into account made up of twenty students and a teacher. During the research, the importance of the application of the experimental method in the teaching-learning process of Natural Sciences was confirmed, since it puts the student in direct contact with learning in a more practical and dynamic way, and also stimulates the students to build their own knowledge.